Research and Experiment on Energy-Conservation Cooling Technique in IDC - Yongshuang, Qiu Wenbo Lin; Yongshuang, Qiu Wenbo Lin (Dianxin kexue)
Beginning with Fourier Law and dealing with centralized and dispersive heat source in server with their merits, the architecture named parallel double-channels was proposed, which consist of “contact-type”and“non-contact-type”channels with significant difference on thermal resistance, and use the “heat pipe water cooling unit + cooling tower”contact-type-cooling-channel to remove the thermal current from the key-chips in server with high efficient. The verification experiment was organized,“the customized server with double-channels-cooling”was developed, and according to the experiment result, it is feasible to realize contact-type-cooling on the CPU in servers with natural cold source.